FRI0090 Pregnancy Outcome of Mothers with Rheumatic Diseases Exposed to Biological Agent during Pregnancy: A Single-Centre Study. (10th June 2014) - Giacuzzo, S.; Padovan, M.; Capucci, R.; Barbieri, M.G.; Govoni, M.
Abstract : Background: Anti-TNFα agents and Rituximab fall within the FDA category B concerning fetal risk. However numerous case series and registry data of pregnancies exposed to these therapies are available in the literature Objectives: Aim of this study was to offer the contribution of our Centre Methods: Data were collected from a prospective single-centre cohort of outpatients followed during pregnancy between 2006 and 2013. Women exposed to biological agent during pregnancy or in the 3 months before conception were included. Outcomes in the biological-exposed group are compared with those in a disease and age-matched group of pregnant women without biological agent exposure. Demographic and clinical data, obstetric outcome and neonatal complications were recorded Results: 26 pregnancies in 21 patients, 10 Rheumatoid Arthritis (RA), 5 ankylosing spondilytis (SA), 3 Psoriatic arthritis (PA), 3 Undifferentiated spondyloarthritis (uSpA) exposed to a biologic agent (13 etanercept, 6 adalimumab, 3 infliximab, 4 RTX) were included. The median age was 33 (range 29-49 yrs), 18 women were nulliparous. All patients a-TNF treated withdrew therapy in early pregnancy (≤10 weeks gestational age). A woman affected by RA became pregnant four times during RTX therapy, respectively 3 months after 3rd retreatment, 2 months after 4th retreatment and 1 month after 5th and 6th retreatment. Only 3 patients were also on DMARDs therapy at time of conceptions, 2 with sulphasalazine (which was continued) and 1 with methotrexate which was immediately withdrawn.12 patients (6 RA, 4 PA, 2 SA) started or increased oral and/or intra-articular steroids during pregnancy because of disease flare. 28 pregnancy in 25 patients were enrolled as control group (12 RA, 9 uSpA, 2 Juvanile Idiopatic Arthritis, 2 PA), median age 34 (range 23-39 yrs).15 patients were treated with DMARDs during pregnancy (sulphasalazine 7;hydroxycloroquine 7, cyclosporine 1). No other drugs were taken at the time of conception, apart from low dose of steroids in 15 cases.Pregnancy outcomes are summarized in tab.1. Therapeutic abortions were performed for extrauterine pregnancy occurred twice in the patient with RA which became pregnant four times during RTX treatment, after the 5th and the 6th retreatment. After the 4th retreatment she had an early spontaneous abortion. Previously, she delivered 2 healthy children after exposure to etanercept and 3th retreatment of RTX. No serious perinatal complication occurred excluding very preterm baby delivery at 28th weeks, who needed neonatal intensive care. No congenital malformations were observed. Klinefelter syndrome was diagnosed in 1 case. Conclusions: Based on these findings, there are no significant differences about pregnancy outcome between biologic-exposed group and non-exposed control group. Additional data from larger numbers of pregnant women exposed to biological agents are required. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3342